2021
DOI: 10.33545/gynae.2021.v5.i1b.792
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of Covid - 19 among mothers during perinatal period: An exploratory study

Abstract: Background: Maternal mental health is a public health concern especially during COVID pandemic. Essential regular Maternity services are affected due to lockdown and fear of its spread. COVID 19 had its psychological impact among general public and also among perinatal mothers. Psychological problems impact perinatal mothers, and are associated with increased risk to mother and the child. Objectives: To study the prevalence of depression, anxiety and stress among perinatal mothers delivering at a tertiary hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Our updated literature search found 35 relevant studies ( Table S1 ). Eight studies each have been reported from Europe and American continents, and 17 studies are reported from Asia, of which only one study ( Anandhi et al, 2021 that assessed anxiety in pregnant women who were COVID positive, compared to those who were COVID negative) was from India. Antenatal anxiety during the COVID-19 pandemic has been found to be related to employment status ( Ceulemans et al, 2021 , Wu et al, 2020 ), educational level ( Effati-Daryani et al, 2020 , Mappa et al, 2020 , Mei et al, 2020 ), income ( Berthelot et al, 2020 , Liu et al, 2020 , Patabendige et al, 2020 , Wu et al, 2020 ), parity ( Hamzehgardeshi et al, 2021 , Ding et al, 2021 , Mappa et al, 2020 , Wu et al, 2020 ) and trimester ( Saadati et al, 2021 , Saccone et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our updated literature search found 35 relevant studies ( Table S1 ). Eight studies each have been reported from Europe and American continents, and 17 studies are reported from Asia, of which only one study ( Anandhi et al, 2021 that assessed anxiety in pregnant women who were COVID positive, compared to those who were COVID negative) was from India. Antenatal anxiety during the COVID-19 pandemic has been found to be related to employment status ( Ceulemans et al, 2021 , Wu et al, 2020 ), educational level ( Effati-Daryani et al, 2020 , Mappa et al, 2020 , Mei et al, 2020 ), income ( Berthelot et al, 2020 , Liu et al, 2020 , Patabendige et al, 2020 , Wu et al, 2020 ), parity ( Hamzehgardeshi et al, 2021 , Ding et al, 2021 , Mappa et al, 2020 , Wu et al, 2020 ) and trimester ( Saadati et al, 2021 , Saccone et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, another study was conducted between July and October 2020 when the public restrictions in India began to be waived off and better management strategies for pregnant became operational. Kotabagi et al also reported that the mean scores of anxiety in pregnant women reduced during the tail end of the pandemic (first wave) [16].Further, access to antenatal care and to outdoor spaces, which were deemed not only to reduce vulnerability to stress but also improve resilience among pregnant women Preis et al were possible during the "unlocking" of public restrictions in India during the study period [17]. The resultant higher sense of well-being and relief after lockdown may have decreased rates of anxiety.…”
Section: Discussionmentioning
confidence: 96%
“…14 Anandhi et al in their study, compared depression, anxiety, and stress among covid positive and negative antenatal women using the Depression, Anxiety and Stress Scale -21 (DASS-21). 15 They found that all pregnant women, irrespective of their COVID status, had a significant psychological impact.…”
Section: Discussionmentioning
confidence: 99%